Political sources: their role in the decision to report - Sáenz Crisóstomo, Maritza Manuela (2020)
This article is based on an analysis of politics and political communication. It focuses mainly on the sources of political information, viewed from various theoretical standpoints and the results of various research, which help to understand their role in the decision to inform.